(NkAPITAN fRAKASS(B:s (NrOMAN (B/s - (NgOTXE t(B.s ((NtEOFILX(B)s; (Nu[AKOW i(B.s ((NmOSKWA(B:s (NpRAWDA(B,s, 1985)
(Nw ROMANE (B"(NkAPITAN fRAKASS(B" (1863), (NPRONIKNUTOM WYSOKIM NRAWSTWENNYM PAFOSOM(B, (NIZWESTNYJ FRANCUZSKIJ PO\T tEOFILX gOTXE (B(1811-1872) (NPOWESTWUET O L@BOWNYH PRIKL@^ENIQH SWOEGO GEROQ(B, (NRAZWERTYWAQ QRKIE KARTINY VIZNI fRANCMM (BXVII (NWEKA(B.s
(NiNW(B.: 245476s
(NtIRAV(B: 500 000 (N\KZ(B.s